Exome sequencing in patients with antiepileptic drug exposure and complex phenotypes. Issue 4 (3rd September 2019) - Jackson, Adam; Ward, Heather; Bromley, Rebecca Louise; Deshpande, Charulata; Vasudevan, Pradeep; Scurr, Ingrid; Dean, John; Shannon, Nora; Berg, Jonathon; Holder, Susan; Baralle, Diana; Clayton-Smith, Jill
Abstract : Introduction: Fetal anticonvulsant syndrome (FACS) describes the pattern of physical and developmental problems seen in those children exposed to certain antiepileptic drugs (AEDs) in utero. The diagnosis of FACS is a clinical one and so excluding alternative diagnoses such as genetic disorders is essential. Methods: We reviewed the pathogenicity of reported variants identified on exome sequencing in the Deciphering Developmental Disorders (DDD) Study in 42 children exposed to AEDs in utero, but where a diagnosis other than FACS was suspected. In addition, we analysed chromosome microarray data from 10 patients with FACS seen in a Regional Genetics Service. Results: Seven children (17%) from the DDD Study had a copy number variant or pathogenic variant in a developmental disorder gene which was considered to explain or partially explain their phenotype. Across the AED exposure types, variants were found in 2/15 (13%) valproate exposed cases and 3/14 (21%) carbamazepine exposed cases. No pathogenic copy number variants were identified in our local sample (n=10). Conclusions: This study is the first of its kind to analyse the exomes of children with developmental disorders who were exposed to AEDs in utero. Though we acknowledge that the results are subject to bias, a significant number of children were identified with alternate diagnoses which had an impact on counselling and management. We suggest that consideration is given to performing whole exome sequencing as part of the diagnostic work-up for children exposed to AEDs in utero.